Sovietinių metų gyvenamieji rajonai Vilniuje: tipiškumo problema - Ruseckaitė, Indrė (Journal of Architecture and Urbanism, 2010)
Soviet period residential districts in Vilnius: problem of typical characterIn the fifties, the Soviet Union witnessed the start of the industrialised wave of massive construction of residential buildings, in the process whereof new urbanism structures emerged in cities and towns. In 1955–1990, the share held by them in Vilnius amounted to some 19 sq km and was called “The New Districts”. Today, the aforementioned districts are referred to as typical faceless bedroom communities. It is the socalled grey face of social modernism or just an imperceptible background for the daily round, the typicality whereof is unquestioning. The report aims at arguing against the aforesaid statement providing a few features that demonstrate a nontypical character of these city districts. wide appreciation, awards for planning Lazdynai and Žirmūnai districts, at least formal listing thereof as urbanism monuments keep from thoughtless application of the template “typical” for the other “new districts” either. The fact that the bedroom communities constitute a typical phenomenon in the former socialist countries is not denied, however, the emphasis on the differences between the districts is supposed to reveal the individual characters thereof. A few bedroom communities of Vilnius are analysed. The start is made from the thing incomprehensible at the present time in the real space of the districts, i.e. the plans and development history thereof. The circumstance that urbanism solutions of all the districts are works of authorship turns to one of the most important considerations. By courtesy of the art of ingenuity and by playing with typical cubes, different urbanism structures of each district are shaped. Freestyle games in the plains, games by the context on the mounds or just the Art of ornamentation in the plan. This is the point where the features of Identification in the role of nontypicality of each district start showing up. They assist in orienting in the city plan identifying clearly the differences between the plans of districts. After shifting the research to the real space and to the present time, by capturing at the level of observer eyes, nontypical character of each district is disclosed through individual architectural details and monolithic concrete highrise accents thereof. These objects become [inter]district guides or marks of Identification in the space. The paper  states that these are the games by nontypical details and/or nontypical buildings in the role of marks of Identification that deny the myth of typicality partially. Current modernization of the districts of the soviet period, however, results in a paradoxical situation when the marks of Identification are leveled down and the former [Non] typical turns to today's Typical.Article in Lithuanian.Santrauka. Straipsnyje nagrinėjami Karoliniškių, Viršuliškių ir Šeškinės gyvenamieji rajonai Vilniuje, išskiriant ir apibūdinant kelis svarbiausius bruožus, leidžiančius teigti, jog šių rajonų urbanistinės architektūrinės charakteristikos tarpusavyje skiriasi ir dėl to šios urbanistinės struktūros nėra tipinės. Analizuojama, kokie buvo rajonus projektavusių architektų kūrybiniai siekiai formuoti individualius rajonų urbanistiniusarchitektūrinius charakterius; kodėl šie rajonai buvo kritikuoti ir kaip į tai reaguojant kito urbanistiniai architektūriniai sprendimai; kaip atnaujinant sovietinio laikotarpio gyvenamuosius rajonus kinta saviti jų požymiai.Reikšminiai žodžiai: sovietiniai metai, masinė statyba, tipiniai pastatai, monolitiniai aukštybiniai gyvenamieji pastatai.